2017
DOI: 10.1063/1.4997423
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared linewidth narrowing in plasmonic Fano-resonant metamaterials via tuning of multipole contributions

Abstract: We report on an experimental and computational (multipole decomposition) study of Fano resonance modes in complementary near-IR plasmonic metamaterials. Resonance wavelengths and linewidths can be controlled by changing the symmetry of the unit cell so as to manipulate the balance among multipole contributions. In the present case, geometrically inverting one half of a four-slot (paired asymmetric double bar) unit cell design changes the relative magnitude of magnetic quadrupole and toroidal dipole contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 50 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…The destructive interference between the fields in adjacent metallic strips led to the subradiant plasmonic modes, which had a weak coupling with the free‐space incident light . Based on the resonance of the SPPs, other periodic metallic nanostructures and the array‐waveguide structures as well as metasurfaces were also designed to realize the Fano resonances . In the array–waveguide structures, the metallic nanostructure arrays were placed or covered by a dielectric layer, which acted as a dielectric waveguide.…”
Section: Mechanisms Of Fano Resonancesmentioning
confidence: 99%
“…The destructive interference between the fields in adjacent metallic strips led to the subradiant plasmonic modes, which had a weak coupling with the free‐space incident light . Based on the resonance of the SPPs, other periodic metallic nanostructures and the array‐waveguide structures as well as metasurfaces were also designed to realize the Fano resonances . In the array–waveguide structures, the metallic nanostructure arrays were placed or covered by a dielectric layer, which acted as a dielectric waveguide.…”
Section: Mechanisms Of Fano Resonancesmentioning
confidence: 99%
“…An approach would be to manipulate the configuration of unit cells in the metamaterial array to mitigate radiative losses. It was reported that by alternating or inverting an asymmetric dipole bars (which constitute to one of the two sub‐unit cells) and placing it adjacent to neighboring asymmetric dipole bars, an enhancement in the Q ‐factor of Fano resonance is achieved. Based on the schematic of dipole–dipole interference, an enhancement in the Q ‐factor of Fano resonance in an alternating unit cell configuration was ascribed to destructive interference of dipole moments contributed by neighboring sub‐unit cells as illustrated in Figure c.…”
Section: Perspectives To Loss Engineeringmentioning
confidence: 99%
“…Quantitative analysis of complementary asymmetric double bars using multipole decomposition reveals that the linewidth narrowing of resonance in an inverted unit cell configuration is due to the competition between magnetic quadrupole and toroidal dipole. In this case, the magnetic quadrupole serves to narrow the resonance linewidth, while the toroidal dipole broadens the resonance linewidth …”
Section: Perspectives To Loss Engineeringmentioning
confidence: 99%
“…Conventional metallic metamaterials suffer from large intrinsic Ohmic losses. The quality factors (Q-factors) of their plasmonic resonances are extremely low [ 11 ], limiting the modulation performance. By comparison, all-dielectric materials offer a potential solution to the issue of intrinsic losses.…”
Section: Introductionmentioning
confidence: 99%